Ecofriendly nonchemical/nonthermal methods for disinfestation and control of pest/fungal infestation during storage of major important cereal grains: A review. Issue 1 (11th February 2021) - Srivastava, Shubhangi; Mishra, Hari Niwas
Abstract: In this review, numerous control methods for stored grain insects are discussed in detail with emphasis on the nonchemical/nonthermal methods. Grain infestation by insects and molds is one of the major problems that need attention as these pests deteriorate the quality of food grains and their products. A number of modern nonchemical methods have been found to be effective against insect pests, such as microwave and infrared heating. Besides those, nonthermal methods, such as ozone treatment and ultraviolet heating, are also gaining importance, as they prove to be much safer tools for the management of pests and molds. In a nutshell, these nonchemical/nonthermal methods have emerged as a plausible alternative to chemical fumigants which may have a deleterious effect on the food product quality from a nutritional point of view. Thus, the objective of this study was to explore the published research works on different control approaches applied on grains for protection against stored insect pests and molds. Three nutritionally and economically important cereal grains, wheat, rice, and maize, which contribute to the world economy in terms of production, are covered in the review. Also, the emphasis is given to the best physical nonchemical methods/nonthermal methods of disinfestation/disinfection of insects and molds: microwave, infrared, and ultraviolet heating as well as ozone treatment. Of all the nonchemical/nonthermal methods, microwave and ozone heating could be possible alternatives for achieving 100% mortality of insects and molds and 50–80% in the case of infrared and ultraviolet provided the grains are at the initial stage of infestation. Abstract : Nonchemical/Nonthermal Methods for Disinfestation & Control of Pest/Fungal Infestation in grains.